THE EFFECT OF PROFITABILITY, LEVERAGE, AND COMPANY SIZE ON TAX AVOIDANCE IN MANUFACTURING COMPANIES LISTED ON THE IDX - Intan Ulia; Jummaini; Ghazali Syamni; Wardhiah (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
This research is to look at the influence of profitability, leverage and company size on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange. 2017-2021 period. Research data can be accessed on the official website www.idx.co.id. The sampling method used purposive sampling and obtained 34 companies. The data analysis technique in this research uses the Panel Data Regression method with the Eviews 10 software tool. This type of research is quantitative research. The data used in this research is secondary data. The data collection technique used in this research using the documentation method was carried out using annual financial report data from manufacturing companies listed on the Indonesian stock exchange. The research results found that the profitability and leverage variables had no effect on tax avoidance, and the company size variable had a positive and significant effect on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange.